A comparative study on the properties of direct current and pulse electroplated copper - Romano, Mark S. (2008)
Copper is the most common metal plated, exclusive of continuous strip plating and nickel. It is electrodeposited for numerous engineering and decorative applications requiring a wide range of mechanical and physical properties. Electroplated copper is playing a major role in the change from aluminum to copper in semiconductor interconnect technology. This signals one of the most important changes in materials that the semiconductor industry has experienced since its creation. This study aims to compare the properties of copper deposited by direct current (DC) electrodeposition and pulse electrodeposition (PED). The effects of factors such as peak current, plating time and electrode distance on grain size, surface morphology, thickness, hardness and uniformity of the deposited layer were determined. SEM images show that DC deposits have larger grain size compared to PED. DC plated copper had large grains since grain growth is the dominant deposition mechanism. PED decreases the growth rate significantly and it can be said that the deposition mechanism is shifted to progressive nucleation leading to uniform deposits. Although the same peak current was used for PED and DC plating, their respective current densities in the study varied greatly, i.e. DC plating had a current density 100 times larger than PED. This caused excessive evolution of hydrogen gas at the cathode and gave DC plated deposits a ?burnt? appearance. Increasing the peak current accelerates the growth rate in DC deposition and causes dendrites to form rapidly resulting in deposits having decreased hardness. According to Faraday?s law, an increase in current density should result in an increase in deposit thickness. However, it was observed that the opposite happened for DC plating, i.e. the thickness dropped with plating time. This anomalous effect is attributed to the increased formation of dendrites which caused the deposited layer to easily shear off during the cleaning step because these structures have poor adhesion and are brittle. The uniformity also dropped because the accelerated growth rate coupled with increased current density at corners cause deposits to form preferentially at these locations. For PED, there was excellent linearity of the deposit thickness with plating time. Increased peak current yielded harder deposits in PED because of an increase in nucleation rate. PED copper had very good adhesion between the deposited layer and the substrate, hence extended plating time resulted in thicker PED copper. For the surface hardness, response, an increase in thickness of the PED copper resulted also to an increase in surface hardness which approached an apparent plateau value with further increase in plating time. This implies that the PED copper is harder than the copper substrate as expected. In the study, the deposited layer was not thick enough to suppress the anvil effect, so the substrate was contributing to the recorded hardness of the deposit. As the deposit thickened, there was less contribution by the substrate and thus the surface hardness was approaching that due to the harder pure PED copper. Varying the electrode distance from 2 cm to 4 cm was found not to have significant effect on the properties of the deposited copper studied in this work.